Pola Asuh Orang Tua dalam Mendampingi Anak Belajar di Rumah Selama Pandemi Covid-19 pada Kelas IV di SD Negeri Sumberejo 2 Bonang Demak - Desi Tri Utami; Husni Wakhyudin; Mira Azizah (STKIP Andi Matappa Pangkep, 2022)
This study aims to describe parenting patterns in assisting children to study at home during the COVID-19 pandemic at SD Negeri Sumberejo 2 Bonang Demak. This type of research is descriptive qualitative. The subjects in this study were homeroom teachers of IVB, parents of 20 students of class IVB. The research was carried out directly at school and by visiting students' and parents' homes by using data collection techniques in the form of interviews, observation, and documentation. The findings of the research results can be concluded that the problems in this study were the many complaints from parents of students with the holding of online learning during the covid-19 pandemic. Problems faced by parents in mentoring learning: parents cannot accompany their children due to their work and busy schedules, limited understanding of the material, economic limitations, disruption of the internet network, and unfavorable conditions due to the large number of family members.